Historical development of hybrid materials - M. R. M., Rejab; Mohammad Hazim, Mohamad Hamdan; Quanjin, Ma; Siregar, J. P.; Bachtiar, Dandi; Muchlis, Yusrizal (Elsevier, 2020)
Hybrid material sourced from nature has existed for billions of years. Nature developed hybridorganic – inorganic materials with exceptional fracture resistance and structural capabilities with complex design (Wegst et al., 2015). Examples of hybrid organic– inorganic materials in nature include bone and narge. Hybrid material sare defined as the combination of organic and inorganic materials, where the range of the hybrid composite is from a few nanometers to tens of nanometers (Mammeri et al., 2005). The organic and inorganic materials result in different properties. The combination of the organic and in organic components in the formation of hybrid materials is limitless (Kickelbick, 2007). Thus, a new combination can lead to a new type of hybrid materials